Escitalopram in preschool-age children diagnosed with obsessive compulsive disorder: A case report - Yazici, Kemal Utku; Percinel, Ipek (Tehran University of Medical Sciences, 2016)
When a literature review on pediatric obsessive-compulsive disorder (OCD) is performed, it is observed that there is a dearth of research on preschool period OCD cases. Although cognitive behavioral therapy is recommended as the first line of treatment in preschool OCD cases when patients do not show adequate response to CBT, psychopharmacological treatment offers an alternative. The first line used in psychopharmacological treatment is selective serotonin reuptake inhibitors (SSRI's). However, no SSRI's (or any other drug group) have been approved by the FDA for this age group. Moreover, studies related to psychopharmacology in preschool OCD are very limited in the literature, consisting mostly of case reports related to sertraline and fluoxetine. In those studies, it is reported that sertraline and fluoxetine are effective in preschool OCD and generally well-tolerated. In this paper, we discussed the treatment and six-month follow-up period of a 3.5 year-old (42 months) female diagnosed with OCD and for whom escitalopram was used. In the literature, there is a retrospective case series related to this subject consisting of eleven cases, where improvement in symptoms is reported with escitalopram treatment in the five of six cases diagnosed with OCD. As far as we could find in literature, our paper is the second report on this subject. Our case also included the youngest patient to receive escitalopram for preschool period OCD and report its benefits.
Keywords: Escitalopram; Obsessive-compulsive disorder; Preschool child